Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Given the piecewise function [tex]\( f(x) \)[/tex]:

[tex]\[ f(x) = \left\{
\begin{array}{ll}
\frac{x^2 - x}{x - 1} & \text{if } x \neq 1 \\
2 & \text{if } x = 1
\end{array}
\right. \][/tex]


Sagot :

Alright, let's carefully explore the function [tex]\( f(x) \)[/tex] defined as follows:

[tex]\[ f(x) = \begin{cases} \frac{x^2 - x}{x - 1} & \text{if } x \neq 1, \\ 2 & \text{if } x = 1. \end{cases} \][/tex]

### Step-by-Step Analysis

1. Evaluate [tex]\( f(x) \)[/tex] for [tex]\( x \neq 1 \)[/tex]:

Let's simplify the expression [tex]\(\frac{x^2 - x}{x - 1}\)[/tex].

The numerator [tex]\( x^2 - x \)[/tex] can be factored:
[tex]\[ x^2 - x = x(x - 1). \][/tex]

Substituting this back into the fraction:
[tex]\[ \frac{x^2 - x}{x - 1} = \frac{x(x - 1)}{x - 1}. \][/tex]

For [tex]\( x \neq 1 \)[/tex], the [tex]\((x - 1)\)[/tex] terms in the numerator and denominator cancel out:
[tex]\[ \frac{x(x - 1)}{x - 1} = x. \][/tex]

Therefore, for [tex]\( x \neq 1 \)[/tex]:
[tex]\[ f(x) = x. \][/tex]

2. Evaluate [tex]\( f(x) \)[/tex] specifically at [tex]\( x = 1 \)[/tex]:

By definition in the function:
[tex]\[ f(1) = 2. \][/tex]

3. Verify the consistency and overall understanding:

- For [tex]\( x \neq 1 \)[/tex], [tex]\( f(x) = x \)[/tex].
- At [tex]\( x = 1 \)[/tex], [tex]\( f(1) = 2 \)[/tex].

4. Example Value Testing:

Let's test the function for a value other than 1 to verify consistency (e.g., [tex]\( x = 2 \)[/tex]):

Substitute [tex]\( x = 2 \)[/tex] into the simplified form:
[tex]\[ f(2) = 2. \][/tex]

### Conclusion

Combining all the information:

- If [tex]\( x \neq 1 \)[/tex], then [tex]\( f(x) = x \)[/tex]. For [tex]\( x = 2 \)[/tex], the function value is [tex]\( f(2) = 2 \)[/tex].
- At [tex]\( x = 1 \)[/tex], the function specifies directly that [tex]\( f(1) = 2 \)[/tex].

Thus, the results for the given conditions are:
[tex]\[ f(1) = 2 \][/tex]
[tex]\[ f(2) = 2 \][/tex]

These results help us confirm that the function behaves as expected at and around [tex]\( x = 1 \)[/tex].